Primary intraosseous meningioma: an osteosclerotic bone tumour mimicking malignancy. Issue 1 (December 2016) - Vlychou, M.; Inagaki, Y.; Stacey, R.; Athanasou, N.
Abstract Background Sclerotic tumours of the calvarial bones are rare and may be due to primary and secondary bone tumours as well as extradural tumours of meningeal origin. Case presentation We report a case of primary intraosseous meningioma (PIM) which arose in the frontal bone of a 63 year old woman who complained of progressive pain and thickening of the right skull. Radiology showed a large osteosclerotic lesion in the right frontal bone. Histology showed an intraosseous lesion containing dense fibrous tissue in which there were scattered cells that expressed epithelial membrane antigen and progesterone receptor. The tumour was partially resected and 3 years after operation has not recurred. Conclusions PIM is a rare tumour which needs to be distinguished from primary/secondary osteosclerotic calvarial bone tumours.